Significance of the leaf area ratio in Hevea brasiliensis under high irradiance and low temperature stress - Ray D; Das G; Dey S K (Photosynthetica, 2004)
Adjustment in leaf area : mass ratio called leaf area ratio (LAR) is one of the strategies to optimize photon harvesting. LAR was recorded for 10 genotypes of Hevea brasiliensis under high irradiance and low temperature and the genotypes were categorized into two groups, i.e. high LAR and low LAR types. Simultaneously, the growth during summer as well as winter periods, photosynthetic characteristics, and in-vitro oxidative damage were studied. Low LAR (19.86+_0.52 m2 kg -1) types, recorded an average of 18.0;chlorophyll (Chl) degradation under high irradiance and 7.1;Chl degradation under low temperature. These genotypes maintained significantly higher net photosynthetic rate (PN) of 10.4 Mmol(CO2)m-2 s-1 during winter season. On the contrary, the ihgh LAR (24.33+_0.27 m2 kg-1) types recorded significantly lower PN of 4 Mmol(CO2) m-2 s-1 and greater Chl degradation of 37.7 and 13.9;under high irradiance and low temperature stress, respectively. Thus LAR may be one of the physiological traits, which are possibly involved in plant acclimation process under both stresses studied.
Keywords: Leaf area ratio; Low temperature stress; Net photosynthetic rate; Photo-oxidative damage; Stomatal conductance